A Comparison of Three Different Positioning Techniques on Surgical Corrections and Postoperative Alignment in Cervical Spinal Deformity (CD) Surgery. Issue 9 (1st May 2021) - Morse, Kyle W.; Lafage, Renaud; Passias, Peter; Ames, Christopher P.; Hart, Robert; Shaffrey, Christopher I.; Mundis, Gregory; Protopsaltis, Themistocles; Gupta, Munish; Klineberg, Eric; Burton, Doug; Lafage, Virginie; et al.
Abstract : Study Design: Retrospective review of a prospective multicenter cervical deformity database. Objective: To examine the differences in sagittal alignment correction between three positioning methods in cervical spinal deformity surgery (CD). Summary of Background Data: Surgical correction for CD is technically demanding and various techniques are utilized to achieve sagittal alignment objectives. The effect of different patient positioning techniques on sagittal alignment correction following CD remains unknown. Methods: Patients with sagittal deformity who underwent a posterior approach (with and without anterior approach) with an upper instrumented vertebra of C6 or above. Patients with Grade 5, 6, or 7 osteotomies were excluded. Positioning groups were Mayfield skull clamp, bivector traction, and halo ring. Preoperative lower surgical sagittal curve (C2–C7), C2–C7 sagittal vertical axis (cSVA), cervical scoliosis, T1 slope minus cervical lordosis (TS–CL), T1 slope (T1S), chin-brow vertebral angle (CBVA), C2–T3 curve, and C2–T3 SVA was assessed and compared with postoperative radiographs. Segmental changes were analyzed using the Fergusson method. Results: Eighty patients (58% female) with a mean age of 60.6 ± 10.5 years (range, 31–83) were included. The mean postoperative C2–C7 lordosis was 7.8° ± 14 and C2–C7 SVA was 34.1 mm ± 15. There were overall significant changes in cervical alignment across the entire cohort, with improvements in T1 slope ( P  < 0.001), C2–C7 ( P  < 0.001), TS–CL ( P  < 0.001), and cSVA ( P  = 0.006). There were no differences postoperatively of any radiographic parameter between positioning groups ( P  > 0.05). The majority of segmental lordotic correction was achieved at C4–5–6 (mean 6.9° ± 11). Additionally, patients who had bivector traction applied had had significantly more segmental correction at C7–T1–T2 compared with Mayfield and halo traction (4.2° vs. 0.3° vs. –1.7° respectively, P  < 0.027). Conclusion: Postoperative cervical sagittal correction or alignment was not affected by patient position. The majority of segmental correction occurred at C4–5–6 across all positioning methods, while bivector traction had the largest corrective ability at the cervicothoracic junction. Level of Evidence: 4 Abstract : Three different cervical positioning techniques were analyzed to examine their effect on postoperative sagittal alignment in cervical deformity patients. Cervical sagittal correction was not affected by patient position and the majority of segmental correction occurred at C4–5–6, while bivector correction obtained the largest corrective ability at the cervicothoracic junction.